Density of Acanthaster planci in the waters of Olele Village - Pius A Arsyad; Femy Sahami; Sri Nuriyatin Hamzah (Faculty of Fishery and Marine Sciences - Universitas Negeri Gorontalo, 2020)
This study aims to determine the density level of Acanthaster planci in Olele Village waters in Kabila Bone District, Bone Bolango Regency. This research was conducted in October 2016 to May 2017. The method used was the Line Intercept Transect (LIT) method with a size of 50 x 5 meters. The research location was divided into 3 stations namely Station I (no influence of human activity), Station II (affected by human activity), and Station III (snorkeling and diving areas). The density was analyzed using the Krebs formula (Napitupulu et al., 2013). The results showed that the population density of Acanthaster planci in the waters of Tomini Gulf, Olele Village, Kabila Bone District is in the alarming or threatening category.